Temperate deciduous shrub and tree In situ autumn phenology 2022 - 2024. Downer Woods, Milwaukee, Wisconsin, USA - Alison Donnelly (PANGAEA, 2025)
This data set includes in situ phenological observations (Day of year) for a range of autumn phenophases (senescence and leaf fall) (2022-2024) for co-occurring species of tree (Tilia americana (American-basswood), Quercus rubra (red-oak), Quercus alba (white-oak) and Acer negundo (boxelder)) Fraxinus spp. (ash) is not included as it has been removed from the site as a result of the Emerald Ash Borer and shrub (Native species: Prunus virginiana (chokecherry), Cornus alternifolia (pagoda-dogwood), Viburnum lentago (nannyberry), Ribes americanum (American-wild-currant) and Euonymus atropurpureus (Eastern wahoo) and Non-native species: Rhamnus cathartica (buckthorn), Lonicera morrowii (honeysuckle), Ligustrum vulgare (European-privet) and Viburnum opulus (European-highbush-cranberry)) in an urban woodland fragment in Wisconsin, USA. Autumn data span 2022 - 2024 whereas corresponding spring data span 2023-2025. The phenophase leaf fall was discontinued in 2023 and therefore data for 2024 is missing.